Environmental friendly power dispatch in Saudi Arabia with renewable energy and energy storage - Pazheri, F. R. (2012)
Optimization of the total amount of pollutants emitted from the hybrid power plants is the main objective of the Environmental Friendly Dispatch (EFD). The EFD problem decides the amount of generation to be allocated to each generating unit including renewable sources so that the total emission of polluting gases is minimized without violating the system constraints. This type of optimization becomes more efficient in countries like Saudi Arabia where high potential of crude oil and renewable resources exists. This paper considers the problem of EFD for hybrid power system including solar, wind and the storage. High potential of solar and wind in Saudi Arabia ensures the availability of renewable sources to some extent. A consistent optimum EFD can be obtained by extracting maximum renewable energy during the available period and using it for both available and unavailable periods with the aid of energy storage. This paper illustrates the optimization of EFD with renewable storage using MATLAB simulation. The simulations have been done using IEEE-30 test bus data with 6 generators.